Imagem e linguagem na pós-história de Vilém Flusser - Rachel Cecilia de Oliveira Costa (2007)
Our dissertation explores philosopher Vilém Flussers concept of posthistory, using his book Pós-história: vinte instantâneos e um modo de usar as base. Our goal is to argue over the possibilities of freedom in a technical society through the explanation of the concept of post-history and the influence such situation exerts. To Flusser this freedom is possible only through art. Optimistically, he applies art as a necessary instrument to modify the situation we find ourselves in. As a consequence, it is possible to reach the conclusion that transcending machines and producing art allows people to acknowledgethemselves as free, capable of doing something on their own, without the use of machines and, thus acknowledging themselves as human beings.